Usefulness of cancer procoagulant (CP) in the detection of renal and bladder cancers - Darewicz, Barbara; Kudelski, Jacek; Gałek, Lech; Gorzel, Małgorzata; Szajda, Sławomir; Domel, Tomasz; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2003)
An early detection of neoplasm is of importance for its successful treatment. To do this biochemical cancer markers are often applied. A cancer procoagulant (CP) whose presence has been lately discovered in the serum of cancer patients but not in healthy persons seems to be the hopeful means to an end. The aim of the investigation was to evaluate the usefulness of CP in renal and bladder cancer detection. The evaluation of CP activity has been determined in 15 patients with renal cancer, 10 patients with bladder cancer and 10 healthy persons (the control group). The CP activity expressed by the coagulation time (in seconds) has been determined according to the Gordon and Benson’s coagulation method. The parameter under investigation in serum of the patients reached a level of 101.0 s±23.4 s for kidney cancer, 79.4 s±17.4 s for bladder cancer and 294.6 s±24.4 s in healthy persons. The CP activity was higher in patients with bladder cancer as compared to those with renal cancer. The said difference was statistically significant (p<0.001). That is why we suggest determining CP activity to be used in the oncological urology diagnostics.